Small MICROplastics (<100 µm) bioindicaToRs in a changing ArctiC EnviRonment (MICROTRACER) - Vitale, Giulia; Vardè, Massimiliano; Caruso, Gabriella; Corami, Fabiani; Rosso, Beatrice; Gregoris, Elena; Iannilli, Valentina; Trotta, Claudia; Lecce, Francesca; Bogialli, Sara; Litti, Lucio; Oliverio, Marco; et al. (CNR-ISP, 2022)
This report refers on fieldwork activity done in August-September 2022 in the framework of the project MICROTRACER (PRA_0005). Sediment samples were collected from 10 sites, located across Krossfjorden and Kongsfjorden, on board of MS Teisten with a grab or manually from the coast. Amphipods were sampled in front of Ny-Alesund harbour and in the coast of the Loven Islands using a hand net. Sediment and Amphipod samples were pre-processed at the Dirigibile Italia laboratories for further chemical and bacteriological analyses to be performed in Italy.